Frantz Fanon, a psychiatrist trapped between anthropology, therapy and revolution: from sociotherapy to anticolonialism - Pérez-Fernández, Francisco; Peñaranda-Ortega, Maria (Anales de Psicología / Annals of Psychology, 2025)
We analyse the anti-colonialist ideas and discourse of Frantz Fanon in an attempt to approach from a different perspective the experience of blackness in the face of the prevailing racism of the time. Fanon (1925-1961), considered the first black psychoanalyst, was a psychiatrist who placed equal importance on the patient's organicity and history, as well as to their politics and culture. He viewed Blackness as a socio-pathological event. The importance lies in how Fanon, throughout the wars, colonialist discourses and events that shaped his life, consolidates an ideological therapy where colonial psychology is the essential basis of analysis and treatment of patients. The emancipation of the coloniser, social revolution and construction of will be fundamental issues for the liberation of the mind. He spent the last years of his short life in Algeria, where he developed a theoretical struggle for mental and anti-colonial revolution and became an important advocate of Algerian freedom. Today, much of the anti-racist and the identity of the skin empowerment discourse echoes his ideas.